2020
DOI: 10.1016/j.foodhyd.2020.106036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein aggregation on rheological properties of pea protein gels

Abstract: Yoghurt style gels are a promising way to increase the consumption of plant derived proteins. However, reaching texture properties similar to those commonly known from milk yoghurts while incorporating large amounts of plant-derived proteins, is a challenge that needs to be addressed to meet consumers expectations. Therefore, this study aims to investigate the influence of pH conditions (pH 6.0 to pH 8.0) during pre-treatment on the rheological properties of fermentation induced pea protein gels with a protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…It has been reported that the faster molecular mobility of solid particles was connected with the frequency-dependent property of G′ and G″ [ 39 ]. Both G′ and G′′ slightly increased as the increasing frequency of oscillating stress, which demonstrated that the characteristic of the Chiba tofu prepared in this study was close to a viscoelastic material [ 40 ]. The G′ and G′′ first increased and latterly slightly decreased with storage periods.…”
Section: Resultsmentioning
confidence: 79%
“…It has been reported that the faster molecular mobility of solid particles was connected with the frequency-dependent property of G′ and G″ [ 39 ]. Both G′ and G′′ slightly increased as the increasing frequency of oscillating stress, which demonstrated that the characteristic of the Chiba tofu prepared in this study was close to a viscoelastic material [ 40 ]. The G′ and G′′ first increased and latterly slightly decreased with storage periods.…”
Section: Resultsmentioning
confidence: 79%
“…PP exhibited an especially notable change in viscosity, increasing up to 497 cp in the 6.2-6.0 pH region. According to Klost et al (2020) [17], the solubility of PP is the lowest at pH 6.0, and Klost and Drusch (2019) [18] reported that the rate of coagulum formation begins to increase at pH 6.2-6.5 as the pH decreases due to the acid produced from LAB fermentation. A maximum rate is achieved at pH 6.0, and then gradually decreases until pH 5.5.…”
Section: Apparent Viscosity Changes According To Ph Following the Physical Treatmentmentioning
confidence: 99%
“…Bi et al found the acid-induced hybrid gels of soy protein and locust bean gum/ĸ-Carrageenan displayed intercycle strain softening behavior in the NLVE regime [144,145]. This behavior was also found when the fermentation-induced pea protein gels were subjected to LAOS tests, but these gels displayed intracycle strain stiffening behavior when the amplitude was between 1.6% and 160%, and intracycle shear thinning behavior when the amplitude exceeded 160% [134,149]. LAOS tests have also been applied on gelatin gels [190,191], waxy rice starch gels [147], pectin-Ca gels [192],…”
Section: Introductionmentioning
confidence: 91%
“…In addition, while the σe of pure WPI gels was near zero for almost the entire cycle when γ0 reached 204%, one could still observe nonzero values for σe when the other gels were subjected to the maximum γ0 (1020%), a sign there was still residual elasticity in the material. That the gels containing SPI showed a slower transition towards plastic properties and still retained an elastic contribution to the response at higher strain, could be another indication of their coarser network structures, since coarser structures are less prone to a complete transition towards plastic behavior due to increased structural flexibility [149]. The higher flexibility could lead to a more gradual decrease in bond numbers, thus some elastic responses can still be detected at higher strain [149].…”
Section: Lissajous Plotsmentioning
confidence: 99%
See 1 more Smart Citation